Editor’s Foreword - Radaev, Vadim (Journal of Economic Sociology, 2020)
Dear colleagues, the very first issue of the Journal of Economic Sociology came out in September 2000, exactly twenty years ago. It was one of the pioneers among the academic e-journals in Russia at the time, when the very notion of ‘electronic journal’ was not widely recognized. We contributed to a new standard, which became quite common many years later